2005
DOI: 10.1088/0029-5515/45/11/013
|View full text |Cite
|
Sign up to set email alerts
|

Transport phenomena in the edge of Alcator C-Mod plasmas

Abstract: Two aspects of edge turbulence and transport in Alcator C-Mod are explored. The quasi-coherent mode (QCM), an edge fluctuation present in Enhanced Dα H-mode plasmas, is examined with regard to its role in the enhanced particle transport found in these plasmas, its in/out asymmetry, its poloidal wave number and its radial width and location. It is shown to play a dominant role in the perpendicular particle transport. The QCM is not observed at the inboard midplane, indicating that its amplitude there is signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 28 publications
10
78
0
Order By: Relevance
“…5 of Ref. 137). It was concluded that the blob birth zone was associated with the gradients rather than with the transition from open to closed field lines.…”
Section: Weak Sheared Flows: Blobs (L-mode)mentioning
confidence: 94%
See 2 more Smart Citations
“…5 of Ref. 137). It was concluded that the blob birth zone was associated with the gradients rather than with the transition from open to closed field lines.…”
Section: Weak Sheared Flows: Blobs (L-mode)mentioning
confidence: 94%
“…126). Finally, a series of L-mode shots on Alcator C-Mod 137 showed that the blob birth zone moved inwards as the normalized density (n e =n G ) was increased, where n G is the Greenwald density limit. For n e =n G > 0:6 the blob birth zone moved inside the separatrix and both the gradients and fluctuation levels inside the separatrix were observed to increase.…”
Section: Weak Sheared Flows: Blobs (L-mode)mentioning
confidence: 99%
See 1 more Smart Citation
“…As the discharge density limit is approached, the far SOL profile becomes broader and the break point moves radially inwards such that the far SOL profile effectively extends all the way to the magnetic separatrix or even inside it. 26 As an illustration of the plasma dynamics in the SOL we present in Fig. 3 the GPI signals at three different radial The PDF of the GPI signals is presented in Fig.…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Under very general conditions, this model predicts a parabolic relation between the skewness and kurtosis moments of the plasma fluctuations. In the case of exponentially distributed burst amplitudes and waiting times, the probability density function for the fluctuation amplitudes is shown to be a Gamma distribution with the scale parameter given by the average burst amplitude and the shape parameter given by the ratio of the burst duration and waiting times.Cross-field transport of particles and heat in the scrape-off layer (SOL) of non-uniformly magnetized plasmas is caused by radial motion of blob-like structures [1][2][3][4][5][6]. This results in singlepoint recordings dominated by large-amplitude bursts, which have an asymmetric wave form with a fast rise and a slow decay, and positively skewed and flattened amplitude probability density functions [7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%